Keeping Oregon Green : Livability, Stewardship, and the Challenges of Growth, 1960-1980 - Larson, Derek R. (Book collections on Project MUSE., 2016)
"Keeping Oregon Green is a new history of the signature accomplishments of Oregon's environmental era: the revitalization of the polluted Willamette River, the Beach Bill that preserved public access to the entire coastline, the Bottle Bill that set the national standard for reducing roadside litter, and the nation's first comprehensive land use zoning law. To these case studies is added the largely forgotten tale of what would have been Oregon's second national park, intended to preserve the Oregon Dunes as one of the country's first National Seashores. Through the detailed study of the historical, political, and cultural contexts of these environmental conflicts, Derek Larson uncovers new dimensions in familiar stories linked to the concepts of 'livability' and environmental stewardship. Connecting events in Oregon to the national environmental awakening of the 1960s and 1970s, the innovative policies that carried Oregon to a position of national leadership are shown to be products of place and culture as much as politics. While political leaders such as Tom McCall and Bob Straub played critical roles in framing new laws, the advocacy of ordinary citizens--farmers, students, ranchers, business leaders, and factory workers--drove a movement that crossed partisan, geographic, and class lines to make Oregon the nation's environmental showcase of the 1970s. Drawing on extensive archival research and source materials, ranging from poetry to congressional hearings, Larson's compelling study is firmly rooted in the cultural, economic, and political history of the Pacific Northwest. Essential reading for students of environmental history and Oregon politics, Keeping Oregon Green argues that the state's environmental legacy is not just the product of visionary leadership, but rather a complex confluence of events, trends, and personalities that could only have happened when and where it did"--